What does structural analysis of the external finance premium say about financial frictions? - Jelena Zivanovic (Bank of Canada, 2019)
I use a structural vector autoregression (SVAR) with sign restrictions to provide conditional evidence on the behavior of the US external finance premium (EFP). The results indicate that the excess bond premium, a proxy for the EFP, reacts countercyclically to supply and monetary policy shocks and procyclically to demand shocks. I confront my empirical evidence with the predictions from financial dynamic stochastic general equilibrium (DSGE) models with respect to the finance premium in order to identify an empirically relevant financial friction. The Bernanke, Gertler and Gilchrist (1999) model generates transmission mechanisms that are favored by the data.
Keywords: E32; E44; 330; Financial markets; Economic models; Recent economic and financialdevelopments